Effects of two host-associated probiotics Bacillus mojavensis B191 and Bacillus subtilis MRS11 on growth performance, intestinal morphology, expression of immune-related genes and disease resistance of Nile tilapia (Oreochromis niloticus) against Streptococcusiniae. (January 2023) - Etyemez Büyükdeveci, Miray; Cengizler, İbrahim; Balcázar, José L.; Demirkale, İbrahim
Abstract: The intensification and diversification of production systems have increased the incidence of diseases, which are usually treated with antibiotics. However, its use should be restricted due to the increasing prevalence of antibiotic-resistant bacteria. Probiotics represent therefore an alternative environmentally friendly strategy for improving growth and disease resistance in aquaculture. Considering that host-derived probiotics may offer greater advantages than those from other environments in terms of safety and efficacy, two potential host-associated probiotic strains ( Bacillus mojavensis B191 and Bacillus subtilis MRS11) were used in the present study, which were previously isolated from intestinal mucus of Nile tilapia ( Oreochromis niloticus ). This study was conducted to assess the effects of dietary administration of two Bacillus strains on growth performance, intestinal morphology, immunity, and disease resistance of Nile tilapia. A total of 375 fish were randomly divided into five groups in triplicate. Nile tilapia were fed a basal diet (control group) or a basal diet supplemented with Bacillus mojavensis B191 (BM) or Bacillus subtilis MRS11 (BS) spores at different concentrations of 1 × 10 6 (BM6 and BS6, respectively) and 1 × 10 8 (BM8 and BS8, respectively) CFU/g of feed for 60 days. Moreover, the survival rate of tilapia upon challenge with Streptococcus iniae was determined following the feeding trial. After the feeding trial, the growth performances were significantly improved in all probiotic-fed groups, with the BS8 group being the highest. Light and electron microscopy observations revealed elevated goblet cells, intestinal villus length (except BM8), microvilli length, microvilli density, and perimeter ratio increase in the intestine of all probiotic-fed groups compared with the control group. Regarding the expression analysis, HSP70 gene was only up-regulated in the BM8 group and a general trend of up-regulation of some immune-related cytokines (TGF-β, IL-10, TNF-α and IL-1β) was observed in all probiotic-fed groups. Likewise, the best protection against Streptococcus iniae was observed in the BS8 group, followed by BS6, BM6 and BM8 groups. Altogether, dietary probiotic supplementation with BS8 and BM6 may improve growth performance, intestinal morphology, immunity, and disease resistance in Nile tilapia. Highlights: Dietary administration of two Bacillus species improved the growth performance of Nile tilapia. Dietary probiotic supplementation improved intestinal morphological features. Dietary probiotic supplementation modulated immune-related genes. Dietary probiotic supplementation enhanced disease resistance against S. iniae.